The Role of Epigenetic Modifications in Cancer Development and Progression: Potential Therapeutic Approaches - Soomro, Imtiaz Ali; Quratulain Badar; Ali , Wajid; khan, Adil; Ali, Syed Rizvan; Mahmood, Waqas (Indus Journal of Bioscience Research, 2025)
This research sought to explore the role of epigenetic changes in cancer initiation and progression, the therapeutic potential of epigenetic modulators, i.e., DNMT inhibitors and HDAC inhibitors, and the expression levels of non-coding RNAs, i.e., miRNAs, in controlling epigenetic changes in cancer cells. The research used a quantitative method, i.e., structured questionnaires and regression analysis to determine the role of epigenetic changes in cancer biology. The research validated that 65% of the respondents were familiar with DNA methylation, 60% with histone modification, and 55% with gene-editing technologies like CRISPR. The Chi-Square analysis validated the presence of significant disparity in awareness among demographic groups, with p-values of 0.02 and 0.05 for awareness of DNA methylation by age and awareness of histone modification by medical specialty, respectively. Regression analysis validated that DNMT inhibitors significantly caused cancer cell apoptosis (β = 0.55, p = 0.0002) and suppressed cancer cell migration (β = -0.30, p = 0.02), while HDAC inhibitors also caused apoptosis (β = 0.47, p = 0.005) and promoted migration inhibition (β = -0.25, p = 0.03). The Chi-Square test of expression of miRNAs further validated significant correlations between miR-21 expression and cancer type (χ² = 10.4, p = 0.02) and between miR-34a expression and DNA methylation (χ² = 12.1, p = 0.01). These results suggest the potential of epigenetic therapies and miRNA-based therapies in controlling cancer cell behavior and enhancing therapeutic efficacy. This study highlights epigenetic modifications in cancer, the potential of DNMT and HDAC inhibitors, and miRNAs, urging further research on optimization.